SCREENING FOR OBESITY AND EDUCATION ON THE IMPACT OF OBESITY IN CHILDREN AT ELEMENTARY SCHOOLS IN NORTH CIKARANG - Syamsiah, Siti; Aenurida, Aenurida (International Journal of Engagement and Empowerment (IJE2), 2025)
The Obesity Screening and Education on the Impact of Childhood Obesity program was successfully conducted at SDN 07 Cikarang Utara in 2025. This activity aimed to identify cases of obesity among elementary school students and raise awareness of the health risks associated with childhood obesity. The screening results indicated that some students were categorized as overweight and obese, highlighting the need for early intervention. The educational session gave students, teachers, and parents insights into the importance of a balanced diet and regular physical activity. Active participation in discussions demonstrated an increased awareness of the health risks of obesity. Based on these findings, it is recommended that schools implement policies that support a healthy lifestyle, encourage nutritious food consumption, and promote student engagement in regular physical activities. Routine obesity screenings and collaboration between schools, healthcare professionals, and the community are essential to ensuring sustainable improvements in children's health.